The Role of Workplace Motivators on Employee Retention in the Insurance Industry of Karnali Province, Nepal - Paudel, Manoj (The Management Review, 2025)
Employee retention reflects an organization’s ability to maintain its workforce over time, minimizing turnover. This study explores the role of workplace motivators in enhancing employee retention within Nepal’s insurance sector, focusing on Karnali Province. Specifically, it assesses how a supportive work environment, training and development opportunities, fair compensation and benefits, and relationships with supervisors and co-workers influence employees’ decisions to stay with their organizations. Data were collected from 335 employees across multiple insurance companies using a structured questionnaire distributed through convenience sampling. Pearson’s correlation and regression analyses were employed to examine the relationships between the independent variables (supportive work environment, training and development, fair compensation, and workplace relationships) and the dependent variable (employee retention). The findings indicate that all four factors significantly and positively impact employee retention. A supportive work environment fosters motivation and comfort, while training and development opportunities enhance engagement and productivity. Fair compensation and benefits serve as key motivators, reducing financial stress and improving job satisfaction. Additionally, positive relationships with supervisors and co-workers strengthen employees’ sense of belonging, further encouraging retention. These results highlight the importance of strategically managing workplace motivators to retain employees and enhance organizational performance. By cultivating a supportive culture, investing in employee growth, offering competitive compensation, and nurturing strong workplace relationships, companies can significantly reduce turnover and sustain a committed workforce.